2020
DOI: 10.3390/rs12172707
|View full text |Cite
|
Sign up to set email alerts
|

New JAXA High-Resolution Land Use/Land Cover Map for Vietnam Aiming for Natural Forest and Plantation Forest Monitoring

Abstract: Highly detailed and accurate forest maps are important for various applications including forest monitoring, forestry policy, climate change, and biodiversity loss. This study demonstrates a comprehensive and geographically transferable approach to produce a 12 category high-resolution land use/land cover (LULC) map over mainland Vietnam in 2016 by remote sensing data. The map included several natural forest categories (evergreen broadleaf, deciduous (mostly deciduous broadleaf), and coniferous (mostly evergre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 73 publications
(104 reference statements)
1
7
0
2
Order By: Relevance
“…Similarly a study in Indonesia [18] found accuracies of 86% using Cband SAR in distinguishing oil palm and acacia plantation from natural forest. Similarly, for S-2 our overall accuracy of 92.5% is similar to previous studies, with 90% accuracy achieved in mapping acacia plantations in Indonesia [66] using optical SPOT satellite (10-20 m resolution) imagery, and 86-88% in Vietnam [23] distinguishing natural forest and plantation (acacia, rubber and eucalyptus combined) using optical and radar data.…”
Section: Plantation and Natural Forest Classificationsupporting
confidence: 86%
See 2 more Smart Citations
“…Similarly a study in Indonesia [18] found accuracies of 86% using Cband SAR in distinguishing oil palm and acacia plantation from natural forest. Similarly, for S-2 our overall accuracy of 92.5% is similar to previous studies, with 90% accuracy achieved in mapping acacia plantations in Indonesia [66] using optical SPOT satellite (10-20 m resolution) imagery, and 86-88% in Vietnam [23] distinguishing natural forest and plantation (acacia, rubber and eucalyptus combined) using optical and radar data.…”
Section: Plantation and Natural Forest Classificationsupporting
confidence: 86%
“…These indices have been proved to be effective in earlier work classifying plantation and natural forest [23,43,44]. Further, we used a form of the radar vegetation index (RVI) [45] We used the results from the time-series (see Section 2.3.1 above) to select 2 vegetation indices: first, the Normalised Burn Ratio (NBR) vegetation index:…”
Section: Sentinel-1 Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several attempts have been made to monitor land cover in the entire VMD, where is covered by clouds up to 93% in peak seasons (Paul Lawson and Zuidema 2009;Li et al 2013;Jackson et al 2018). Truong et al and Hoang et al have successfully quantified comprehensive land cover in the delta, using the fusion of multiple remotely sensed sources (Truong et al 2019;Hoang et al 2020). However, these results contain relatively a few misclassifications among non-forest classes such as barren land and open water.…”
Section: Potential Of Eluc For Large-scale Usementioning
confidence: 99%
“…Implementing multispectral data, studies have long been conducted, especially in oil palm plantations 6 or rubber estates. 7 While multispectral is invaluable for rural mapping, problems of atmospheric disturbances such as cloud cover remain, especially when the changing climate is considered. The option of using synthetic aperture radar (SAR) has been investigated in an attempt to solve these problems.…”
Section: Introductionmentioning
confidence: 99%